Kajian Teknis Sistem Penyaliran Tambang Terbuka Pada Penambangan Batubara Blok B PT Minemex Indonesia Desa Talang Serdang Kecamatan Mandiangin Kabupaten Sarolangun Provinsi Jambi - Randi Sepniko; Murad Murad; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. This study discusses optimal solution to handle water entering coal mining Block B PT.Minemex Indonesia. Water comes from ground water and surface runoff that floods the groundfloor of the mining work area, causing coal cannot be carried out. To determination runoff andgroundwater discharge into the mining, we have to know its debit. We also determinatedimensions of open channel, sump, and settling pond, and also capacity of the pump used. Theresults, pit B mining PT. Minemex Indonesia has a total catchment area of 47.3 ha withmaximum daily rainfall of 94,44 mm/day. Total debit is 1,22651 m3/second, maximum capacity ofsump is 85.775 m3, with 123 m x 123 m surface dimensions, and 116 m x 116 m at the base and6 m depth. The trapezoidal-shaped open channel sare located on the mining front to drain thewater to sump, and near the settling pond to drain the pumped water from the sump to thesettling pond. By using HDPE pipes and 3 units Coates HL-200 centrifugal pumps that have 63meters maximum head and 107 liters/second maximum pumping debit, water will be pumpedinto settling pond which has 5 compartments and 10.400,4 m3 overall volume.Keywords: Catchment Area, Rainfall, Sump, Pump, Settling Pond